The critical role of timely medical emergency team activation in oncological and non-oncological patients - Kaspar F. Bachmann; Samuel J. Michimura; Luca Cioccari; Joerg C. Schefold; Anna S. Messmer (PLoS ONE, 2025)
Purpose This study aimed to analyse the impact of time from first physiological derangement (positive Vital Sign Score, VSS) to Medical Emergency Team (MET) activation on mortality in oncological versus non-oncological patients. Methods All in-hospital patients requiring a MET assessment were included. The primary outcome was 30-day mortality. Subanalyses were performed for the population that was admitted to the ICU as well as the subgroups of oncological with solid vs. haematological cancer. In addition, we assessed the number and time points of VSS measurements in oncological and non-oncological patients. Results 286 out of 4068 (8.9%) documented MET calls were attributed to oncological patients. Each hour delay from first abnormal VSS to MET activation was associated with an 3% increase in adjusted 30-day all-cause mortality odds (OR 1.03, 95% CI 1.02–1.05, p < 0.001), independent of oncological status (interaction p = 0.141). Oncological patients had a significantly higher number of vital sign measurements on the ward (median 24 [16–37] vs 18 [10–27], p < 0.001) before MET activation, and higher 30-day all-cause mortality (38.1% vs 21.8%, p < 0.001). Conclusions Although the overall outcome did not differ between, oncological patients comprised 10% of MET calls, had higher mortality and had significantly more frequent vital sign monitoring, reflecting greater clinical concern. Tailored monitoring including early MET review has potential to improve outcomes particularly in high-risk oncological patients.